Preparation method of alloy aluminum ingot containing nano material

By adding specific elements and nanomaterials to the alloy aluminum ingot, casting and annealing treatment, and using corrosion inhibitors, the problems of insufficient hardness and easy corrosion of the alloy aluminum ingot are solved, achieving high hardness and good corrosion inhibition effect of the material.

CN119571126AInactive Publication Date: 2025-03-07JIANGSU JIAQUN METAL TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411877929.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-03-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing alloy aluminum ingots are insufficient hardness and are prone to corrosion during use, which poses safety hazards and is difficult to effectively alleviate.

Method used

A nanomaterial-containing alloy aluminum ingot is prepared by adding copper, manganese, silicon, nanoalumina and iron into the furnace, and casting and annealing are carried out after completely melting, and a special corrosion inhibitor is used to process it to form a dense oxide film to prevent corrosion.

Benefits of technology

It improves the hardness and impact toughness of alloy aluminum ingots, while significantly enhancing its resistance to corrosion, ensuring the stability and safety of the long-term use of the material.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of alloy aluminum ingots, and discloses a preparation method of an alloy aluminum ingot containing a nanometer material, the preparation method comprises the following steps: adding an aluminum ingot into a smelting furnace, heating, and slagging off after the aluminum ingot is completely smelted to obtain an intermediate 1; adding copper, manganese, silicon, nano aluminum oxide and iron into the smelting furnace filled with the intermediate 1, and completely melting to obtain an intermediate 2; adding the intermediate 2 into a cavity of a casting grinding tool, and casting to obtain an intermediate 3; the intermediate 3 is put into an annealing furnace to be annealed and then put into a corrosion inhibitor to be soaked, and an alloy aluminum ingot containing the nanometer material is obtained after soaking is finished; after annealing is finished, a corrosion inhibitor is used for treating the aluminum alloy ingot, imidazole, quaternary ammonium salt and nanometer aluminum oxide contained in the corrosion inhibitor have a corrosion inhibition effect, a compact oxidation film can be formed on the surface of the aluminum alloy ingot, contact of corrosive media such as moisture and oxygen is blocked, and the synergistic effect plays a role in corrosion inhibition on the aluminum alloy ingot; and the hardness of the aluminum alloy ingot can be improved by the contained nano aluminum oxide.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of alloy aluminum ingots, and in particular to a method for preparing an alloy aluminum ingot containing nanomaterials. Background Art

[0002] Alloy aluminum ingots are made from pure aluminum and recycled aluminum, and then mixed with other elements such as silicon, iron, copper, and silicon. They are widely used in the manufacture of transportation vehicles such as trains, cars, spacecraft, and rockets. However, if the hardness is insufficient during use, it will pose a safety hazard. During long-term use, water and oxygen in the air will cause corrosion to their surface. How to avoid this phenomenon is the key to solving the problem. For example, patent CN104131203A discloses an aluminum-zinc alloy composite material containing nano-silicon for hot-dip plating and its preparation method. The resulting nano-composite material has good ductility and formability and has potential applications in hot-dip plating, but it does not improve its corrosion inhibition effect. Summary of the Invention

[0003] (1) Technical problems solved In view of the shortcomings of the existing technology, the present invention provides a method for preparing an alloy aluminum ingot containing nanomaterials, which has good hardness and impact toughness, and has the property of preventing the alloy aluminum ingot from corrosion.

[0004] (2) Technical solution To achieve the above object, the present invention provides the following technical solution: a method for preparing an alloy aluminum ingot containing nanomaterials, comprising the following steps: (1) Add 50-70 parts by weight of aluminum ingots into a furnace, heat to 700-800°C, and skim off the slag after all the aluminum ingots are melted to obtain an intermediate 1; (2) adding 2-3 parts by weight of copper, 1-4 parts by weight of manganese, 2-5 parts by weight of silicon, 1.2-3 parts by weight of nano-alumina, and 1.4-5 parts by weight of iron to a melting furnace containing 40-65 parts by weight of the intermediate 1, and completely melting the mixture to obtain the intermediate 2; (3) adding 35-50 parts by weight of the intermediate 2 into the mold cavity of a casting mold and casting the mold at a casting speed of 60-70 mm / min, controlling the cooling water pressure of the casting mold at 0.06-0.1 MPa, and controlling the cooling water temperature of the casting mold at 22-34°C to obtain the intermediate 3; (4) 40-45 parts by weight of the intermediate 3 is placed in an annealing furnace for 6-9 hours at a temperature of 580-615°C, and then immersed in 80-110 parts by weight of a corrosion inhibitor for 15-30 minutes to obtain an alloy aluminum ingot containing nanomaterials.

[0005] Preferably, the temperature of the furnace in (2) is 710-720°C.

[0006] Preferably, the preparation method of the corrosion inhibitor in (3) is: S1. The nano-alumina was ultrasonically dispersed into a mixed solution of anhydrous ethanol and deionized water, mixed evenly, and γ-aminopropyltriethoxysilane was added. The reaction was carried out at 30-50 ° C for 6-10h. After the reaction, the reaction was centrifuged, washed, and dried to obtain amino-treated nano-alumina. S2 was added to N, N- dimethylformamide solvent 3-6 parts by weight of amino nano-alumina and 5-8 parts by weight of 2,3-epoxypropyltrimethylammonium chloride, stirred to dissolve, the reaction was carried out at 75-90 ℃ for 8-10h, and then distilled under reduced pressure, filtered and dried to obtain quaternized nano-alumina; S3. 4-hydroxy-5-methyl-1,3-benzenedicarboxylic acid and 3,3-diaminobenzidine were added to a reactor, followed by the addition of polyphosphoric acid. Nitrogen was introduced for protection and mechanical stirring was performed at 160-190° C. for 22-25 hours. After completion, the reaction was cooled, washed with deionized water, filtered, neutralized with 8-12% by mass ammonia water, filtered, washed with water until neutral, and dried to obtain hydroxylated polybenzimidazole. S4. Acetone solvent was added to the reactor, nitrogen was introduced, and hydroxylated polybenzimidazole and phosphorus oxychloride were added thereto. The reaction was carried out at 30-50 ° C for 4-9 hours. After the reaction, ice water was added, concentrated, and extracted with ethyl acetate. The organic phase was dried over anhydrous magnesium sulfate, the filtrate was concentrated, washed with ether, and then recrystallized from ethyl acetate to obtain a modified polybenzimidazole. S5. Add quaternized nano-alumina and modified polybenzimidazole to N,N-dimethylformamide solvent, stir and react at 90-110°C for 6-8h, and then distill under reduced pressure, filter and dry to obtain a corrosion inhibitor.

[0007] Preferably, the mass ratio of nano-alumina to γ-aminopropyltriethoxysilane in S1 is 1:1.1-1.3.

[0008] Preferably, the mass ratio of 4-hydroxy-5-methyl-1,3-phthalic acid, 3,3-diaminobenzidine and polyphosphoric acid in S3 is 1.1-1.5:1:0.01-0.03.

[0009] Preferably, the mass ratio of hydroxylated polybenzimidazole to phosphorus oxychloride in S4 is 1:2.2-3.

[0010] Preferably, the mass ratio of quaternized nano-alumina to modified polybenzimidazole in S5 is 1.3-1.5:1.

[0011] (3) Beneficial technical effects The present invention comprises the following steps: adding an aluminum ingot into a melting furnace, heating it, and skimming off the slag after it is completely melted to obtain an intermediate 1; adding copper, manganese, silicon, nano-alumina, and iron into the melting furnace containing the intermediate 1, and completely melting them to obtain an intermediate 2; adding the intermediate 2 into a mold cavity of a casting mold and casting to obtain an intermediate 3; placing the intermediate 3 in an annealing furnace for annealing, and then soaking it in a corrosion inhibitor to obtain an alloy aluminum ingot containing nano-materials.

[0012] After annealing, it is treated with a corrosion inhibitor. The imidazole, quaternary ammonium salt and nano-alumina contained in the corrosion inhibitor have a corrosion inhibition effect and will form a dense oxide film on the surface of the alloy aluminum ingot, blocking the contact of corrosive media such as moisture and oxygen. The synergistic effect has a corrosion inhibition effect on the alloy aluminum ingot; the nano-alumina contained in it can increase the hardness of the alloy aluminum ingot. DETAILED DESCRIPTION Example 1

[0013] (1) 50 parts by weight of an aluminum ingot is added to a furnace, heated to 700°C, and slag is removed after all the aluminum ingot is melted to obtain an intermediate 1; (2) Add 2 parts by weight of copper, 1 part by weight of manganese, 2 parts by weight of silicon, 1.2 parts by weight of nano-alumina, and 1.4 parts by weight of iron into a melting furnace containing 40 parts by weight of intermediate 1. The temperature of the melting furnace is 710°C. After complete melting, intermediate 2 is obtained. (3) 35 parts by weight of the intermediate 2 was added to the mold cavity of the casting mold and cast at a casting speed of 60 mm / min, the cooling water pressure of the casting mold was controlled at 0.06 MPa, and the cooling water temperature of the casting mold was controlled at 22°C to obtain the intermediate 3; (4) Ultrasonic dispersion of nano-alumina into a mixed solution of anhydrous ethanol and deionized water, uniformly mixed, and then adding γ-aminopropyltriethoxysilane, wherein the mass ratio of nano-alumina to γ-aminopropyltriethoxysilane is 1:1.1, reacting at 30°C for 6 hours, centrifugation washing, and drying after the reaction to obtain amino-treated nano-alumina; (5) Add 3 parts by weight of amino-treated nano-alumina and 5 parts by weight of 2,3-epoxypropyltrimethylammonium chloride to N,N-dimethylformamide solvent, stir and dissolve, react at 75°C for 8 hours, and then distill under reduced pressure, filter and dry to obtain quaternized nano-alumina; (6) 4-hydroxy-5-methyl-1,3-benzenedicarboxylic acid and 3,3-diaminobenzidine were added to the reactor, and then polyphosphoric acid was added, wherein the mass ratio of 4-hydroxy-5-methyl-1,3-benzenedicarboxylic acid, 3,3-diaminobenzidine and polyphosphoric acid was 1.1:1:0.01, nitrogen was introduced for protection, mechanical stirring was performed, and the reaction was carried out at 160°C for 22 hours. After the reaction, the mixture was cooled, washed with deionized water, filtered, neutralized with 8% ammonia water, filtered, washed with water until neutral, and dried to obtain hydroxylated polybenzimidazole; (7) Add acetone solvent to the reactor, pass nitrogen protection, add hydroxylated polybenzimidazole and phosphorus oxychloride, wherein the mass ratio of hydroxylated polybenzimidazole to phosphorus oxychloride is 1:2.2, react at 30°C for 4 hours, add ice water after the reaction, concentrate, add ethyl acetate for extraction, dry the organic phase over anhydrous magnesium sulfate, concentrate the filtrate, wash with ether, and then recrystallize with ethyl acetate to obtain modified polybenzimidazole; (8) Quaternized nano-alumina and modified polybenzimidazole were added to N,N-dimethylformamide solvent, wherein the mass ratio of quaternized nano-alumina to modified polybenzimidazole was 1.3:1, and the mixture was stirred at 90°C for 6 hours. After the reaction, the mixture was distilled under reduced pressure, filtered and dried to obtain a corrosion inhibitor.

[0014] (9) 40 parts by weight of the intermediate 3 was placed in an annealing furnace for 6 hours at an annealing temperature of 580°C, and then placed in 80 parts by weight of a corrosion inhibitor and soaked for 15 minutes. After the annealing, an alloy aluminum ingot containing nanomaterials was obtained. Example 2

[0015] (1) 70 parts by weight of aluminum ingots were added to a furnace, heated to 800°C, and slag was removed after all the aluminum ingots were melted to obtain an intermediate 1; (2) Add 3 parts by weight of copper, 4 parts by weight of manganese, 5 parts by weight of silicon, 3 parts by weight of nano-alumina, and 5 parts by weight of iron into a melting furnace containing 65 parts by weight of intermediate 1. The temperature of the melting furnace is 720°C. After complete melting, intermediate 2 is obtained. (3) 50 parts by weight of the intermediate 2 was added to the mold cavity of the casting mold and cast at a casting speed of 70 mm / min, the cooling water pressure of the casting mold was controlled at 0.1 MPa, and the cooling water temperature of the casting mold was controlled at 34°C to obtain the intermediate 3; (4) Ultrasonic dispersion of nano-alumina into a mixed solution of anhydrous ethanol and deionized water, uniformly mixed, and then adding γ-aminopropyltriethoxysilane, wherein the mass ratio of nano-alumina to γ-aminopropyltriethoxysilane is 1:1.3, reacting at 50°C for 10 hours, centrifugation washing, and drying after the reaction to obtain amino-nano-alumina; (5) Add 6 parts by weight of amino-type nano-alumina and 8 parts by weight of 2,3-epoxypropyltrimethylammonium chloride to N,N-dimethylformamide solvent, stir and dissolve, react at 90°C for 10 hours, and then distill under reduced pressure, filter and dry to obtain quaternized nano-alumina; (6) 4-hydroxy-5-methyl-1,3-benzenedicarboxylic acid and 3,3-diaminobenzidine were added to the reactor, and then polyphosphoric acid was added, wherein the mass ratio of 4-hydroxy-5-methyl-1,3-benzenedicarboxylic acid, 3,3-diaminobenzidine and polyphosphoric acid was 1.5:1:0.03, nitrogen was introduced for protection, mechanical stirring was performed, and the reaction was carried out at 190°C for 25 hours. After the reaction, the mixture was cooled, washed with deionized water, filtered, neutralized with 12% ammonia water, filtered, washed with water until neutral, and dried to obtain hydroxylated polybenzimidazole; (7) Add acetone solvent to the reactor, pass nitrogen protection, add hydroxylated polybenzimidazole and phosphorus oxychloride, wherein the mass ratio of hydroxylated polybenzimidazole to phosphorus oxychloride is 1:3, react at 50°C for 9 hours, add ice water after the reaction, concentrate, add ethyl acetate for extraction, dry the organic phase over anhydrous magnesium sulfate, concentrate the filtrate, wash with ether, and then recrystallize with ethyl acetate to obtain modified polybenzimidazole; (8) Quaternized nano-alumina and modified polybenzimidazole were added to N,N-dimethylformamide solvent, wherein the mass ratio of quaternized nano-alumina to modified polybenzimidazole was 1.5:1, and the mixture was stirred at 110°C for 8 hours. After the reaction, the mixture was distilled under reduced pressure, filtered and dried to obtain a corrosion inhibitor.

[0016] (9) 45 parts by weight of the intermediate 3 was placed in an annealing furnace for 9 hours at an annealing temperature of 615°C, and then placed in 110 parts by weight of a corrosion inhibitor and soaked for 30 minutes. After the annealing, an alloy aluminum ingot containing nanomaterials was obtained. Example 3

[0017] (1) 60 parts by weight of aluminum ingots were added to a furnace, heated to 750°C, and slag was removed after all the aluminum ingots were melted to obtain an intermediate 1; (2) Add 2.5 parts by weight of copper, 2.5 parts by weight of manganese, 3.5 parts by weight of silicon, 2.1 parts by weight of nano-alumina, and 2.7 parts by weight of iron to a melting furnace containing 52.5 parts by weight of intermediate 1. The temperature of the melting furnace is 715°C. After complete melting, intermediate 2 is obtained. (3) 42.5 parts by weight of the intermediate 2 was added to the cavity of the casting mold and cast at a casting speed of 65 mm / min, a cooling water pressure of the casting mold was controlled at 0.08 MPa, and a cooling water temperature of the casting mold was controlled at 28°C to obtain the intermediate 3; (4) Ultrasonic dispersion of nano-alumina into a mixed solution of anhydrous ethanol and deionized water, uniformly mixed, and then adding γ-aminopropyltriethoxysilane, wherein the mass ratio of nano-alumina to γ-aminopropyltriethoxysilane is 1:1.2, reacting at 40°C for 8 hours, centrifugation washing, and drying after the reaction to obtain amino-treated nano-alumina; (5) Add 4.5 parts by weight of amino-treated nano-alumina and 6.5 parts by weight of 2,3-epoxypropyltrimethylammonium chloride to N,N-dimethylformamide solvent, stir and dissolve, react at 82.5°C for 9 hours, and then distill under reduced pressure, filter and dry to obtain quaternized nano-alumina; (6) 4-hydroxy-5-methyl-1,3-benzenedicarboxylic acid and 3,3-diaminobenzidine were added to the reactor, and then polyphosphoric acid was added, wherein the mass ratio of 4-hydroxy-5-methyl-1,3-benzenedicarboxylic acid, 3,3-diaminobenzidine and polyphosphoric acid was 1.3:1:0.02, nitrogen was introduced for protection, mechanical stirring was performed, and the reaction was carried out at 175°C for 23.5h. After the reaction, the mixture was cooled, washed with deionized water, filtered, neutralized with 10% ammonia water, filtered, washed with water until neutral, and dried to obtain hydroxylated polybenzimidazole; (7) Add acetone solvent to the reactor, introduce nitrogen protection, add hydroxylated polybenzimidazole and phosphorus oxychloride, wherein the mass ratio of hydroxylated polybenzimidazole to phosphorus oxychloride is 1:2.6, react at 40°C for 6.5 hours, add ice water after the reaction, concentrate, add ethyl acetate for extraction, dry the organic phase over anhydrous magnesium sulfate, concentrate the filtrate, wash with ether, and then recrystallize with ethyl acetate to obtain modified polybenzimidazole; (8) Quaternized nano-alumina and modified polybenzimidazole were added to N,N-dimethylformamide solvent, wherein the mass ratio of quaternized nano-alumina to modified polybenzimidazole was 1.4:1, and the mixture was stirred at 100°C for 7 hours. After the reaction, the mixture was distilled under reduced pressure, filtered and dried to obtain a corrosion inhibitor.

[0018] (9) 42.5 parts by weight of the intermediate 3 was placed in an annealing furnace for 7.5 hours at an annealing temperature of 597.5°C, and then placed in 95 parts by weight of a corrosion inhibitor and immersed for 22.5 minutes to obtain an alloy aluminum ingot containing nanomaterials.

[0019] Comparative Example 1 (1) 60 parts by weight of aluminum ingots were added to a furnace, heated to 750°C, and slag was removed after all the aluminum ingots were melted to obtain an intermediate 1; (2) Add 2.5 parts by weight of copper, 2.5 parts by weight of manganese, 3.5 parts by weight of silicon, 2.1 parts by weight of nano-alumina, and 2.7 parts by weight of iron to a melting furnace containing 52.5 parts by weight of intermediate 1. The temperature of the melting furnace is 715°C. After complete melting, intermediate 2 is obtained. (3) 42.5 parts by weight of the intermediate 2 was added to the cavity of the casting mold and cast at a casting speed of 65 mm / min, a cooling water pressure of the casting mold was controlled at 0.08 MPa, and a cooling water temperature of the casting mold was controlled at 28°C to obtain the intermediate 3; (4) 42.5 parts by weight of the intermediate 3 was placed in an annealing furnace for 7.5 hours at a temperature of 597.5°C to obtain an alloy aluminum ingot containing nanomaterials.

[0020] Comparative Example 2 (1) 60 parts by weight of aluminum ingots were added to a furnace, heated to 750°C, and slag was removed after all the aluminum ingots were melted to obtain an intermediate 1; (2) Add 2.5 parts by weight of copper, 2.5 parts by weight of manganese, 3.5 parts by weight of silicon, and 2.7 parts by weight of iron to a melting furnace containing 52.5 parts by weight of intermediate 1. The temperature of the melting furnace is 715°C. After complete melting, intermediate 2 is obtained. (3) 42.5 parts by weight of the intermediate 2 was added to the cavity of the casting mold and cast at a casting speed of 65 mm / min, a cooling water pressure of the casting mold was controlled at 0.08 MPa, and a cooling water temperature of the casting mold was controlled at 28°C to obtain the intermediate 3; (4) 42.5 parts by weight of the intermediate 3 was placed in an annealing furnace for 7.5 hours at an annealing temperature of 597.5°C, and then placed in 95 parts by weight of a corrosion inhibitor and soaked for 22.5 minutes. After the annealing, an alloy aluminum ingot containing nanomaterials was obtained.

[0021] The hardness is measured according to the national standard GB3849-1983 "Test method for Rockwell hardness (A scale) of cemented carbide"; the impact toughness of the alloy is measured according to the national standard GB / T1817-1995 "Test method for room temperature impact toughness of cemented carbide". Impact toughness.

[0022] Table 1: Hardness and toughness tests.

[0023] project Hardness / HRA <![CDATA[Impact toughness / (J / cm 2 )]]> Example 1 86.71 4.602 Example 2 88.23 4.679 Example 3 86.31 4.457 Comparative Example 1 82.36 4.234 Comparative Example 2 72.19 2.103 As shown in Table 1, Comparative Example 2 does not contain nano-alumina. Compared with Comparative Example 2, Examples 1-3 of the present invention have better hardness and impact toughness. Determination of the corrosion inhibition performance of the corrosion inhibitor: Using 12% hydrochloric acid as the corrosive medium, the corrosion inhibition performance of Examples 1-3 and Comparative Examples 1-2 was determined by a 4h corrosion coupon test at 90°C using the product of the present invention. The corrosion inhibitor dosage was 1000ppm. The results are shown in Table 2.

[0024] Table 2: Corrosion inhibition performance test.

[0025] project Surface morphology Corrosion inhibition rate (%) Example 1 Smooth and flat 95.21 Example 2 Smooth and flat 96.37 Example 3 Smooth and flat 96.19 Comparative Example 1 Slightly uneven 71.34 Comparative Example 2 Smooth and flat 93.16 As can be seen from Table 2, the aluminum alloy ingots containing nanomaterials of Examples 1-3 of the present invention have better corrosion inhibition effects than Comparative Example 1.

[0026] The preferred embodiments of the present invention disclosed above are intended only to help illustrate the present invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the present invention to the specific embodiments described. Obviously, many modifications and variations are possible based on the content of this specification. These embodiments are selected and described in detail in this specification to better explain the principles and practical applications of the present invention, thereby enabling those skilled in the art to better understand and utilize the present invention. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for preparing an alloy aluminum ingot containing nanomaterials, characterized in that: The following steps are involved: (1) adding 50-70 parts by weight of aluminum ingots into a melting furnace, heating to 700-800° C., and skimming the slag after all the aluminum ingots are melted to obtain an intermediate 1; (2) adding 2-3 parts by weight of copper, 1-4 parts by weight of manganese, 2-5 parts by weight of silicon, 1.2-3 parts by weight of nano-alumina, and 1.4-5 parts by weight of iron into a melting furnace containing 40-65 parts by weight of the intermediate 1, and after complete melting, obtaining the intermediate 2; (3) adding 35-50 parts by weight of the intermediate 2 into the mold cavity of a casting mold, casting the mold at a casting speed of 60-70 mm / min, controlling the cooling water pressure of the casting mold at 0.06-0.1 MPa, and controlling the cooling water temperature of the casting mold at 22-34° C. to obtain an intermediate 3; (4) 40-45 parts by weight of the intermediate 3 is placed in an annealing furnace for annealing for 6-9 hours at a temperature of 580-615°C, and then placed in 80-110 parts by weight of a corrosion inhibitor for 15-30 minutes to obtain an alloy aluminum ingot containing nanomaterials.

2. The method for preparing an alloy aluminum ingot containing nanomaterials according to claim 1, characterized in that: The temperature of the furnace in (2) is 710-720°C.

3. The method for preparing an alloy aluminum ingot containing nanomaterials according to claim 1, characterized in that: The preparation method of the corrosion inhibitor in (3) is: S1. Ultrasonic dispersion of nano-alumina into a mixed solution of anhydrous ethanol and deionized water, after mixing evenly, adding γ-aminopropyltriethoxysilane, reacting at 30-50°C for 6-10h, centrifugation washing after the reaction, and drying to obtain amino nano-alumina; S2. Add 3-6 parts by weight of amino nano-alumina and 5-8 parts by weight of 2,3-epoxypropyltrimethylammonium chloride to N,N-dimethylformamide solvent, stir to dissolve, react at 75-90 ° C for 8-10h, and then distill under reduced pressure, filter and dry to obtain quaternized nano-alumina; S3. Add 4-hydroxy-5-methyl-1,3-phthalic acid and 3,3-diaminobenzidine to the reactor, then continue to add polyphosphoric acid, introduce nitrogen for protection, mechanically stir, react at 160-190° C. for 22-25 hours, cool after completion, wash with deionized water, filter, neutralize with 8-12% ammonia water by mass, filter, wash with water until neutral, and dry to obtain hydroxylated polybenzimidazole; S4. Add acetone solvent to the reactor, pass nitrogen protection, add hydroxylated polybenzimidazole and phosphorus oxychloride thereto, react at 30-50° C. for 4-9 hours, add ice water after the reaction, concentrate, add ethyl acetate for extraction, dry the organic phase over anhydrous magnesium sulfate, concentrate the filtrate, wash with ether, and then recrystallize with ethyl acetate to obtain modified polybenzimidazole; S5. Add quaternized nano-alumina and modified polybenzimidazole to N,N-dimethylformamide solvent, stir and react at 90-110°C for 6-8h, and then perform reduced pressure distillation, filter and dry to obtain a corrosion inhibitor.

4. The method for preparing an alloy aluminum ingot containing nanomaterials according to claim 3, characterized in that: The mass ratio of nano-alumina to γ-aminopropyltriethoxysilane in S1 is 1:1.1-1.

3.

5. The method for preparing an alloy aluminum ingot containing nanomaterials according to claim 3, characterized in that: The mass ratio of 4-hydroxy-5-methyl-1,3-phthalic acid, 3,3-diaminobenzidine and polyphosphoric acid in S3 is 1.1-1.5:1:0.01-0.

03.

6. The method for preparing an alloy aluminum ingot containing nanomaterials according to claim 3, characterized in that: The mass ratio of hydroxylated polybenzimidazole to phosphorus oxychloride in S4 is 1:2.2-3.

7. The method for preparing an alloy aluminum ingot containing nanomaterials according to claim 3, characterized in that: The mass ratio of quaternized nano-alumina to modified polybenzimidazole in S5 is 1.3-1.5:1.

Citation Information

Patent Citations

  • Nanometer silicon-containing Al-Zn alloy composite material used for hot dipping and preparation method thereof

    CN104131203A